IKAN GABUS TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM DI KLINIK KASIH BUNDA LUBUKLINGGAU - Hanifa, Fanni; Yulandari, Novalinda; Sugesti, Retno (Poltekkes Kemenkes Maluku, 2024)
Background : Injury to the perineum occurs when a tear occurs in the birth canal during the natural birth process or as a result of surgical removal of the pericardium during childbirth. In general, wounds on the perineum are usually located in the middle of the perineum and can expand due to various factors such as rapid labor in the lower part, uncontrolled labor, body imbalances, problems with abdominal tissue, birth of large babies, internal problems. presentation of the baby, shoulder dystocia, cuts to the epigastrium, and possibly other factors. Objective: To determine the effect of snakehead fish on the healing of perineal wounds in post-partum mothers at the Kasih Bunda Clinic, Lubuklinggau in 2023. Method: The method used in this research is a case study which involves a series of activities related to collecting data from various sources, including libraries, reading, note-taking and research document management. Conclusion: There is